Prospects for new physics searches at the LHC in the forward proton mode - Fichet, Sylvain [UNESP] (Jagiellonian University, 2015)
The installation of forward proton detectors at the LHC will provide the possibility to observe central exclusive processes, opening a novel window on physics beyond the Standard Model. We review recent developments about the discovery potential from central exclusive light-by-light scattering. The search for this process is expected to provide bounds on a wide range of new particles, and turns out to be complementary from the new physics searches in central detectors.